(3JOQjH GdLeHGR GdeYGUQs - (3TMGJg eMeO EHQGgjes ((3GdbGgQIs (3OGQ GdacQ GdYQHjs, 2003)
(3JWQb Edi CgejI JYde COGA GdegGQGJ aj GdLeHGR h GNJjGQ GdehghHjf dJfejI bOQGJge efO GdUZQ Ke JfGhd Cge GdEUGHGJ h ELQGAGJ GdCef h GdhbGjI efgG hQcR Ydi CSGSjGJ heHGOF GdJOQjH GdQjGVj ddfGTFjf CgejI hVY NWI JOQjH h EYOGO GdQjGVj HOfjG hfaSjG(B.s